Gene therapy: an emerging therapy for hair cells regeneration in the cochlea - Wang, Jipeng; Zheng, Jianwei; Wang, Haiyan; He, Haoying; Li, Shuang; Zhang, Ya; Wang, You; Xu, Xiaoxiang; Wang, Shuyi (Frontiers in Neuroscience, 2023)
Sensorineural hearing loss, which is typically caused by damage to the cochlear hair cells (HCs) due to external stimuli or because of one’s genetic factors and the inability to convert sound mechanical energy into nerve impulses. Adult mammalian inner ear HCs cannot regenerate spontaneously; therefore, this type of deafness is usually considered irreversible. Studies on the developmental mechanisms of HC differentiation have revealed that nonsensory cells in the cochlea acquire the ability to differentiate into HCs after the overexpression of specific genes, such as Atoh1, which makes HC regeneration possible. Gene therapy, through in vitro selection and editing of target genes, transforms exogenous gene fragments into target cells and alters the expression of genes in target cells to activate the corresponding differentiation developmental program in target cells. This review summarizes the genes that have been associated with the growth and development of cochlear HCs in recent years and provides an overview of gene therapy approaches in the field of HC regeneration. It concludes with a discussion of the limitations of the current therapeutic approaches to facilitate the early implementation of this therapy in a clinical setting.